An investigation on flashing instability induced water hammer in an open natural circulation system. (November 2016) - Hou, Xiaofan; Sun, Zhongning; Su, Jiqiang; Fan, Guangming
Abstract: The flashing instability induced water hammer phenomenon (FIIWH) is firstly found in an open natural circulation experimental facility, which is used to study the thermalhydraulics characteristic of natural circulation style PCS. The primary mechanism of the FIIWH is that, the periodic movement of flashing front in the upwards channel leads to the periodic violent changes of the local pressure and temperature at the underpart of upwards channel. However, the pressure change rate is more rapid than temperature, which causes the alternately transforms of water from superheated and subcooled at the underpart of upwards channel, and results in the periodic violent evaporation and steam condensation process there. Among them, the rapid condensation causes the sudden acceleration and collision of water columns and forms a transient high pressure peak i.e. the FIIWH. Besides, the horizontal tube at the underpart of upwards channel (pipeline structure) also makes an essential effect on the FIIWH. Furthermore, the influence factors on the region and intensity of FIIWH, e.g. the heating tube outlet temperature, inlet subcooling, loop structure and non-condensable gas in water are experimental studied in detail. The initial and terminal conditions of the FIIWH are also found out by experiments. And the contour map describing the scope and intensity of the FIIWH are drawn in this paper. Finally, a simplified numerical model is carried out to simulate the pressure peak of the FIIWH. The simulation result shows a good agreement with the experimental result on the low inlet subcooling conditions, while it has a disparity with the experiment result on the high inlet subcooling conditions. And the deviation reason and improvement orientation of the model are analyzed in this paper. Highlights: A kind of flashing instability induced water hammer (FIIWH) is observed firstly. The mechanism of FIIWH is investigated by experiments. The occurrence and influence factors of FIIWH are figured out by experiments. A simple simulation model is carried out to calculate the pressure peak induced by FIIWH.